Lower Extremity Mechanics and Pathomechanics of People with Patellofemoral Syndrome: A Review - Mohsen Barghamdi; Leila Sabouri (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2023)
Introduction: The purpose of this study was to review the research conducted on biomechanical and pathomechanical variables of the limbs of people with patellofemoral syndrome and also to summarize and present information in a useful framework from past researches. Methods: The present study was systematic review. Keywords included: mechanics, pathomechanics of the lower limb, kinetics, kinematics, center of pressure and Electromyographic activity of lower limbs, patellofemoral syndrome on the sites of Google  Scholar, Science Direct, Web of science, PubMed and Magiranwas searched  One hundred nine articles were obtained by using the keywords of the study, and according to the intended purpose and removing duplicate articles, 48 articles were obtained, and according to the desired purpose, in the three parts of the patellofemoral joint, Plantar pressure variables and surrounding patellofemoral muscles were classified and analyzed in terms of mechanics, damage, forces on the joint, electrical activity of muscles and equipment used in the research in the form of tables and text. Results: Displacement of the center of pressure in people with patellofemoral syndrome during using orthotics with corrective exercises was reduced. The main cause of pain in patellofemoral syndrome was the delay in the activity of vastus medialis and vastus lateralis muscles relative to each other, which caused the abnormal displacement of the patella to the side and as a result increased the pressure on the patellofemoral joint and eventually caused pain. Closed kinetic chain exercises and biofeedback strengthened the mentioned muscles. Conclusion: Knowledge of the function of patellofemoral joint elements and orthoses and corrective exercises can help the mechanics and pathomechanics of people with patellofemoral syndrome.